2021
DOI: 10.1002/aelm.202001284
|View full text |Cite
|
Sign up to set email alerts
|

Boosting the Thermoelectric Properties of PEDOT:PSS via Low‐Impact Deposition of Tin Oxide Nanoparticles

Abstract: materials' efficiency to convert heat into electricity remains still quite low in the low-temperature range. To quantify the TE performances, the figure of merit zT is introduced, which is described by the equation = σ κ zT S T 2 , [4,5] where σ is the electrical conductivity, S the Seebeck coefficient, κ the thermal conductivity, and T the absolute temperature. Due to the intrinsically low thermal conductivity of polymeric TE materials, the power factor, which is described as PF = σS 2 , is the main factor to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 47 publications
1
24
0
Order By: Relevance
“…The increase in the electrical conductivity has been commonly attributed to the phase separation between PEDOT and PSS promoted by EG, which acts as a binder between PEDOT grains, facilitating charge transport. [ 14 ] Regarding the samples containing also the tin species, the mechanism behind the conductivity variation could be attributed to the interaction between Sn ions with oxygen from PSS − and the Coulombic interaction between PEDOT+ and the nanoparticles, as it has been recently suggested by Dong et al [ 26 ] . Some other authors reported an improvement in the thermoelectric performance of hybrid composites formed by PEDOT:PSS and Si nanoparticles owing to the changes in the polymeric molecular ordering involving increased Seebeck coefficient and reduced thermal conductivity.…”
Section: Resultsmentioning
confidence: 90%
See 2 more Smart Citations
“…The increase in the electrical conductivity has been commonly attributed to the phase separation between PEDOT and PSS promoted by EG, which acts as a binder between PEDOT grains, facilitating charge transport. [ 14 ] Regarding the samples containing also the tin species, the mechanism behind the conductivity variation could be attributed to the interaction between Sn ions with oxygen from PSS − and the Coulombic interaction between PEDOT+ and the nanoparticles, as it has been recently suggested by Dong et al [ 26 ] . Some other authors reported an improvement in the thermoelectric performance of hybrid composites formed by PEDOT:PSS and Si nanoparticles owing to the changes in the polymeric molecular ordering involving increased Seebeck coefficient and reduced thermal conductivity.…”
Section: Resultsmentioning
confidence: 90%
“…In contrast, PEDOT:PSS has also been mixed either with carbon allotropies [23] or Bi or Se-based compounds [8,24] to improve its thermoelectric performance, while the use of oxide fillers such as ZnO [25] or SnO x has only been recently suggested. [26] In this work, both n-type SnO 2 and p-type SnO nanoparticles have been used as fillers in PEDOT:PSS-based hybrid layers, the performance of which were investigated in gas sensing and thermoelectrics. It is worth noting that p-type semiconducting binary oxides, such as SnO, are scarce, contrary to their n-type counterparts, hence their use is still underexplored despite their great potential.…”
Section: Doi: 101002/pssa202100794mentioning
confidence: 99%
See 1 more Smart Citation
“…The rapid development of flexible and wearable electronics puts forward high requirements for wearable power supply systems. Thermoeletric (TE) devices, which can harvest energy from the human body heat and convert it into electric power, have gained considerable attention because they can be used to provide energy for wearable devices sustainably and uninterruptedly. To realize flexible and wearable application, various fiber-based TE devices were designed and prepared due to their advantages of flexibility, wearing comfort, and designable structure. Based on former studies, most fiber-based TE devices are obtained by combining fabrics with various TE materials, such as the poly­(3,4-ethylenedioxythiophene):poly­(styrenesulfonate) (PEDOT:PSS), poly­(3-hexylthiophene) (P 3 HT), PbTe, Sb 2 Te 3 , and Bi 2 Te 3 . Compared with the brittle inorganic TE materials, the use of conducting polymers such as PEDOT, polythiophene (PTh), and polypyrrole (PPy) as coating layers to construct fiber-based TE devices offers numerous advantages of great flexibility, light weight, and low thermal conductivity. Typically, PEDOT:PSS is the most commonly used organic TE material, which has high electrical conductivity, water solubility, and easy processability. , …”
Section: Introductionmentioning
confidence: 99%
“…16−18 Typically, PEDOT:PSS is the most commonly used organic TE material, which has high electrical conductivity, water solubility, and easy processability. 19,20 In order to be wearable, the fiber-based TE materials must be flexible enough to withstand the friction and bending during body movement, so as to reduce the unstable and attenuated performances. 21 However, pristine PEDOT:PSS has a Young's modulus of ∼500 MPa and a maximum tensile strain (ε) of ∼5%, making it too hard and brittle to be stably used in wearable TE devices.…”
Section: Introductionmentioning
confidence: 99%